Utility of COVID‐19 antigen testing in the emergency department. Issue 1 (15th January 2022) - Peacock, W. Frank; Soto‐Ruiz, Karina M.; House, Stacey L.; Cannon, Chad M.; Headden, Gary; Tiffany, Brian; Motov, Sergey; Merchant‐Borna, Kian; Chang, Anna Marie; Pearson, Claire; Patterson, Brian W.; Jones, Alan E.; et al.
Abstract: Background: The BinaxNOW coronavirus disease 2019 (COVID‐19) Ag Card test (Abbott Diagnostics Scarborough, Inc.) is a lateral flow immunochromatographic point‐of‐care test for the qualitative detection of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) nucleocapsid protein antigen. It provides results from nasal swabs in 15 minutes. Our purpose was to determine its sensitivity and specificity for a COVID‐19 diagnosis. Methods: Eligible patients had symptoms of COVID‐19 or suspected exposure. After consent, 2 nasal swabs were collected; 1 was tested using the Abbott RealTime SARS‐CoV‐2 (ie, the gold standard polymerase chain reaction test) and the second run on the BinaxNOW point of care platform by emergency department staff. Results: From July 20 to October 28, 2020, 767 patients were enrolled, of which 735 had evaluable samples. Their mean (SD) age was 46.8 (16.6) years, and 422 (57.4%) were women. A total of 623 (84.8%) patients had COVID‐19 symptoms, most commonly shortness of breath ( n = 404; 55.0%), cough ( n = 314; 42.7%), and fever ( n = 253; 34.4%). Although 460 (62.6%) had symptoms ≤7 days, the mean (SD) time since symptom onset was 8.1 (14.0) days. Positive tests occurred in 173 (23.5%) and 141 (19.2%) with the gold standard versus BinaxNOW test, respectively. Those with symptoms >2 weeks had a positive test rate roughly half of those with earlier presentations. In patients with symptoms ≤7 days, the sensitivity, specificity, and negative and positive predictive values for the BinaxNOW test were 84.6%, 98.5%, 94.9%, and 95.2%, respectively. Conclusions: The BinaxNOW point‐of‐care test has good sensitivity and excellent specificity for the detection of COVID‐19. We recommend using the BinasNOW for patients with symptoms up to 2 weeks.